Revolutionizing anti-tumor therapy: unleashing the potential of B cell-derived exosomes - Xiong, Jingwen; Chi, Hao; Yang, Guanhu; Zhao, Songyun; Zhang, Jing; Tran, Lisa Jia; Xia, Zhijia; Yang, Fang; Tian, Gang (Frontiers in Immunology, 2023)
B cells occupy a vital role in the functioning of the immune system, working in tandem with T cells to either suppress or promote tumor growth within the tumor microenvironment(TME). In addition to direct cell-to-cell communication, B cells and other cells release exosomes, small membrane vesicles ranging in size from 30-150 nm, that facilitate intercellular signaling. Exosome research is an important development in cancer research, as they have been shown to carry various molecules such as major histocompatibility complex(MHC) molecules and integrins, which regulate the TME. Given the close association between TME and cancer development, targeting substances within the TME has emerged as a promising strategy for cancer therapy. This review aims to present a comprehensive overview of the contributions made by B cells and exosomes to the tumor microenvironment (TME). Additionally, we delve into the potential role of B cell-derived exosomes in the progression of cancer.